ECG FINDINGS IN PULMONARY EMBOLISM OR PSEUDO INFARCTION PATTERN - Stefanovic, Ivana; Tamburkovski, Vlada; Kascak, Jelena; Andjelic, Sladjana (Halo 194 Scientific Journal of Emergency Medicine, 2022)
Introduction/objective The differential diagnosis of ST elevation includes 4 major conditions: MI, pericarditis, early repolarization syndrome, secondary changes, and other diagnoses such as pulmonary embolism (PE). Our goal is to acquaint the doctor with making the right decision. Case report The 84-year-old patient called HMP because of chest pain and difficulty breathing. She was found lying flat, pale and sweaty, but currently. She had hip surgery, on fraxiparin therapy. BP 90/60mmHg, HR 115 / min, RR is 20 / min, SpO2 70%, normal frequency and vesiculary breahing. ECG: ST elevation in D2, D3, and AVF, with depression in D1, AVL, V2-6, as well as S1Q3T3. Conclusion: Coronary angiography per se will not harm these patients, but delaying PE therapy can be fatal. Of great importance is ECG monitoring, where the regression of ECG changes, and the loss of Q tooth favors PE.